Subcutaneous fat necrosis in two newborns treated with induced hypothermia. - Farinelli, P.; Miglino, B.; Boldorini, R.; Colombo, E. (European Journal of Pediatric Dermatology, 2011)
Subcutaneous fat necrosis (SCFN) is a rare cutaneous disorder of the newborn occurring in full-term or post-mature neonates who experienced a perinatal distress (3). SCFN is a transient condition of unknown origin. (6). Two cases of SCFN possibly favored by induced hypothermia were reported.